Evaluation of the socially evaluated cold-pressor group test (SECPT-G) in the general population - Becker, Linda; Schade, Ursula; Rohleder, Nicolas (PeerJ, 2019)
Background In stress research, economic instruments for introducing acute stress responses are needed. In this study, we investigated whether the socially evaluated cold-pressor group test (SECPT-G) induces salivary alpha-amylase (sAA) and/or cortisol responses in the general population and whether this is associated with anthropometric, experimental, and lifestyle factors. Methods A sample of 91 participants from the general population was recruited. Salivary cortisol and sAA levels were assessed prior to (t0), immediately after (t1), and 10 min after the SECPT-G (t2). Results A robust cortisol increase was found immediately after the SECPT-G, which further increased between t1 and t2. This was independent of most of the control variables. However, men showed a trend toward higher cortisol increases than women (p = 0.005). No sAA responses were found at all. However, sAA levels were dependent on measurement time point with highest levels between 9 pm and 9:30 pm. Participants who immersed their hands into the ice water for the maximally allowed time of 3 min showed higher sAA levels at all time points than participants who removed their hands from the water earlier. Conclusions We conclude that the SECPT-G is a good means of an acute stress test when cortisol—but not necessarily sAA—responses are intended.
Keywords: SECPT; Stress; Groups; Cortisol; Alpha-amylase; Sympathetic nervous system; HPA axis; General population; Lifestyle factors; Stress test